The method of prohibition in the Book of Purification from Sunan Al- Nasa’i, An applied rhetorical study - Esmat, Abdel-Hanan (Journal of Humanities & Social Sciences, 2020)
The research was monitored under the title: (The Method of Forbidding in the Book of Purification from Sunan Al- Nisai, An Applied Rhetorical Study) Although rhetorical and grammatical theories are apparent, they serve one goal, It is to preserve the tongue in Arabic speech or to speak the case as necessary, so it is considered a means to tighten the legal rulings, but it has been sufficient for many to learn it only without applying it in the legal texts, especially in the noble Hadith, for this reason I traced this modest study so that the topic is more accurate As an illustration in a few separate pages for students to benefit from in the easiest opportunity and in the least possible time, it became clear to me through this study that the end has a high position and high importance in the science of grammar and rhetoric, and when applied in the content of the hadiths of the Prophet, he reaches the desired goal. It is worth noting that I found in the research, hadiths that contain the method of prohibition (3) hadiths, And the reason for the lack of hadiths that include the prohibition, the Messenger- may God bless him and grant him peace- was building judgments with wisdom and good advice, and it was not heavy-hearted for the companions around the companions and the Islamic nation to be dispersed, but- peace and blessings be upon him- was attained with the mercy of God be blessed and exalted, and he was wise Islamic Nation. This study monitored citizen aspects of the statement of the method of prohibition and its application in the Book of Purification from Sunan Al-Nasa’i, so that this work is a prelude to me to do the same work in the future in all prophetic traditions, and it became clear to me after examination, study and analysis that it is indispensable to know this method in the texts of the noble prophetic traditions in The sites, in turn, determine the grammatical and rhetorical meanings for which they were established, and the results of the research are shown as follows: And the Messenger- may God’s prayers and peace be upon him- has increased many of the construction methods by adopting a means to express his ideas issued intentionally and intentionally, and this is due to the enjoyment of these methods and workmanship due to their effective role and ability to report and achieve understanding, The study showed that the position of the prohibition is a high position because the legal rulings include the prohibition. The prohibition of other methods is not less important because it includes the purpose that is to direct the Companions to finish an act, as well as discipline them, and the tendency to adopt the methods of prohibition was one of the most prominent formal characteristics prominent in the hadiths of the Prophet; Because the Messenger- may God’s prayers and peace be upon him- cared to the two addressees in the succession of prohibiting methods to provoke them, and they were persuaded to do what was assigned to them.